Effect of noise on human performance in data entry task / Zahid A. Khan, Jamaluddin Abdullah and W. M. Wan Muhamad - A. Khan, Zahid; Abdullah, Jamaluddin; Wan Muhamad, W. M. (Faculty of Mechanical Engineering & UiTM Press, 2005)
Studies on the effect of noise on human performance involving various kinds of tasks such as cognitive, analytical, and memory have been conducted for long. However, the effect remains both elusive and interesting. All kinds of results, suggesting improved, degraded and unaffected performance, have been reported. The present study reports the effect of intermittent noise on data entry task of short duration. The study was conducted at four levels of noise intensity, viz 70 dBA Leq, 80 dBA Leq, and 100 dBA Leq. The noise used was actually sharp sound beads at a frequency of 60 ± 5 beads per minute. A total of 10 young male subjects participated in the study. The results show an improvement of performance, especially at moderately higher levels of noise intensity. Conjectured reason for such behaviour and suggestions for further research are given.